Предмет: Алгебра,
автор: Mikanka
помогите пожалуйста! )
Срочно!
Приложения:
Ответы
Автор ответа:
0
1) (x + 2)³ = x³ + 8
(x + 2)³ = (x + 2)(x² - 2x + 4) делим на (x + 2) ≠ 0, x ≠ - 2
(x + 2)² = x² - 2x + 4
x² + 4x + 4 = x² - 2x + 4
6x = 0
x = 0
2) (3x - 1)³ = 27x³ - 1
(3x - 1)³ = (3x - 1)(9x² + 3x + 1) делим на (3x - 1) ≠ 0, x ≠ 1/3
(3x - 1)² = 9x² + 3x + 1
9x² - 6x + 1 = 9x² + 3x + 1
- 6x - 3x = 0
- 9x = 0
x = 0
(x + 2)³ = (x + 2)(x² - 2x + 4) делим на (x + 2) ≠ 0, x ≠ - 2
(x + 2)² = x² - 2x + 4
x² + 4x + 4 = x² - 2x + 4
6x = 0
x = 0
2) (3x - 1)³ = 27x³ - 1
(3x - 1)³ = (3x - 1)(9x² + 3x + 1) делим на (3x - 1) ≠ 0, x ≠ 1/3
(3x - 1)² = 9x² + 3x + 1
9x² - 6x + 1 = 9x² + 3x + 1
- 6x - 3x = 0
- 9x = 0
x = 0
Автор ответа:
0
Спасибо большое! !
Похожие вопросы
Предмет: Химия,
автор: Аноним
Предмет: Химия,
автор: vanfd
Предмет: Математика,
автор: amanbekovemir5
Предмет: Математика,
автор: Хотэй
Предмет: Литература,
автор: tuny